Molecular phylogeny resolves a taxonomic misunderstanding and places Geisleria close to Absconditella s. str. (Ostropales: Stictidaceae) - Aptroot, Andre; Parnmen, Sittiporn; Luecking, Robert; Baloch, Elisabeth; Jungbluth, Patricia [UNESP]; Caceres, Marcela E. S.; Lumbsch, H. Thorsten (Cambridge University Press, 2014)
The phylogenetic position of the genus Geisleria and its type species G. sychnogonioides was reconstructed using sequence data of the mitochondrial small subunit (mtSSU), the nuclear large subunit rDNA (nuLSU) and the first subunit of the RNA polymerase (RPB1). The species, previously classified in Verrucariaceae (Eurotiomycetes) and Strigulaceae (Dothideomycetes), is sister to the type of the genus Absconditella, A. sphagnorum, and nested within the genera Absconditella and Cryptodiscus combined (which also includes the lichenized Bryophagus). At first glance it appears to be a further example of parallel evolution of perithecioid ascomata within Stictidaceae (Lecanoromycetes: Ostropales), besides Ostropa and Robergea, adding to the growing list of perithecioid forms nested within apothecioid lineages in Ostropomycetidae, and specifically Ostropales, with other examples known from Graphidaceae (several genera), Gyalectaceae (Belonia), and Porinaceae. However, revision of type material collected by Nitschke revealed that the species actually develops typical apothecia with a narrowly exposed disc. We conclude that Geisleria sychnogonoides was erroneously considered a pyrenocarpous taxon, because in dry conditions the apothecia are closed and not recognizable as such. The species usually grows on unstable soil and therefore often only develops young, more or less closed ascomata (yet with mature ascospores), and has also been confused with the superficially similar Belonia incarnata, in which the ascomata remain closed even when mature. Geisleria sychnogonioides has so far only been known as a rarely reported pioneer species from loamy soils in Europe and North America. Here it is reported to occur abundantly on lateritic soils in subtropical Brazil, suggesting that it is cosmopolitan and possibly common, but much overlooked.
Keywords: crustose; lichen; perithecia; systematics; taxonomy; tropical